2021
DOI: 10.1097/ceh.0000000000000323
|View full text |Cite
|
Sign up to set email alerts
|

Continuing Education Outcomes for Advance Care Planning: A Systematic Review of the Literature

Abstract: Introduction: Advance care planning (ACP) is a process of considering future health and care needs for a time when a person may be unable to speak for themselves. Health professional continuing education programs have been proposed for facilitating patient participation in ACP; however, their impacts on participants, patient and clinical outcomes, and organizational approaches to ACP are not well understood. Methods: This systematic literature review ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…In addition, attendees of CE courses show a significant improvement in their confidence as a result of their attendance. This result was consistent across fields including medical providers, nurses, social workers, and students 35 …”
Section: Introductionsupporting
confidence: 69%
See 3 more Smart Citations
“…In addition, attendees of CE courses show a significant improvement in their confidence as a result of their attendance. This result was consistent across fields including medical providers, nurses, social workers, and students 35 …”
Section: Introductionsupporting
confidence: 69%
“…31 Several research studies have supported this theory by demonstrating the most effective approach to adult education is the use of multimodal techniques that rely on goal-oriented, active learning strategies. [32][33][34][35] Additionally, these principles of constructivism align nicely with radiology education. Multiple studies have shown that the most effective, evidence-based approach to teaching radiology is active learning, particularly case-based (CBL) or team-based learning (TBL).…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…Although the dialog is important in ACP practice and should begin when the patient can still participate in such discussions, it has become clear that many physicians and nurses in Japan do not want to initiate discussions before the patient’s condition worsens [ 10 ]. Moreover, although the conversation between patients and specialists in the field of palliative care is [ 11 ], the practice of such is reportedly difficult, and few educational programs on ACP practice have been confirmed effective [ 12 ].…”
Section: Introductionmentioning
confidence: 99%